Antimicrobial peptides from plants: stabilization of the γ core of a tomato defensin by intramolecular disulfide bond‡. (19th February 2013) - Avitabile, C.; Capparelli, R.; Rigano, M. M.; Fulgione, A.; Barone, A.; Pedone, C.; Romanelli, A.; Morelli, Giancarlo
<x xml:space="preserve">Abstract</x> Cysteine‐containing antimicrobial peptides of diverse phylogeny share a common structural signature, the γ core, characterized by a strong polarization of charges in two antiparallel β sheets. In this work, we analyzed peptides derived from the tomato defensin SolyC07g007760 corresponding to the protein γ core and demonstrated that cyclization of the peptides, which results in segregation of positive charges to the turn region, produces peptides very active against Gram negative bacteria, such as Salmonella enterica and Helicobacter pylori. Interestingly, these peptides show very low hemolytic activity and thus represent a scaffold for the design of new antimicrobial peptides. Copyright © 2013 European Peptide Society and John Wiley & Sons, Ltd.